Implementasi Corporate Social Responsibility (CSR) Perspektif Etika Bisnis Islam (Studi Perusahaan Kalla A Group Of Companies) - harni harni harni; Mustakim mustakim (Jurnal Ilmiah Ekonomi Islam, 2023)
Corporate Social Responsibility (CSR) is interpreted as the company's commitment to participate in sustainable economic development in order to improve the quality of life and the environment that is beneficial, both for the company itself, the local community and society. Corporate social responsibility basically has a broad meaning, not limited to social responsibility towards employees and stakeholders, but social responsibility towards the environment, the surrounding community and the general public. The purpose of this research is to find out how the implementation of Corporate Social Responsibility (CSR) in Kalla A Group of Companies in the Perspective of Islamic Business Ethics. This type of research is a type of qualitative research, with data sources using Secondary Data, namely collecting data indirectly through the Company's official website, books, journals, articles, and previous studies. The results of the study show that the implementation of CSR for Kalla A Group of Companies does not yet cover the health sector, but includes education, social, Islamic community development and the economy. Furthermore, the implementation of CSR in Kalla A Group of Companies is in accordance with Islamic Business Ethics, because in implementing CSR the Company has implemented 10 Principles of Islamic Business Ethics.